Research of the effectiveness of mechanical testing methods with analysis of features of destructions and temperature effects - A.V. Babushkin; D.S. Lobanov; A.V. Kozlova; I.D. Morev (Fracture and Structural Integrity)
In this paper is carried out the comparative analysis of effectiveness of test methods of determination of stiffness and strength properties of highly filled unidirectional fiberglass (Direct "E" roving 0.7 - orthophthalic polyester resin 0.3) via tensile testing along the reinforcement and three-point bending testing at several bases. The necessity of deviation from standard procedures is substantiated. Deformation and failure features of the material under quasi-static loading, as well as at low and high temperatures, are shown.